Kepemimpinan Kepala Daerah Perempuan dan Dinamika Konflik Pertambangan di Kabupaten Jombang - Fanda Amalia Putri (Brawijaya University, 2024)
The capability and leadership of women local governments in handling mining conflicts is an interesting discourse in gender research because the issue of mining conflicts is often labeled as a masculine issue. For this reason, the author tries to present research on the leadership of women in local government in handling the dynamics of illegal C-excavation mining conflicts in Jombang Regency. This study aims to describe how women in local governments handle the dynamics of illegal quarrying conflicts in Jombang Regency from an ecofeminism perspective. The leadership of the Jombang Regent in handling the illegal C-excavation mining conflict was then analyzed using two theories: ecofeminism and gender and conflict theory. Both theories are used to examine women's capabilities in managing the environment, as well as the position and role of women in handling conflicts. The research method used is qualitative, involving interviews and literature studies in data collection. This study found that under Mundjidah Wahab's leadership, several efforts were made to address illegal mining activities and conflicts. Some of these efforts include conducting monitoring, socializing environmental impacts and criminal threats to miners, resolving existing conflicts with a persuasive approach, and efforts to make legal products as a solution to overcome illegal c-excavation mining activities, which are the root of the conflict. Although various obstacles in its implementation cause the handling process to be suboptimal, its achievements need to be appreciated. The steps taken by Mundjidah have proven the relevance of ecofeminism theory, which gives confidence to women as actors who care and are most capable of managing the environment.